Countering Radicalism For Millennials In Cyberface In The 5.0 Era - Kharismah Gulsani; Muhammad Thalal; Dini Kartika; Apriliah (UIN Mataram, 2026)
The purpose of this paper is to counteract radicalism for millennials in the cyberface era 5.0, to work on qualitative methods, and to quote from secondary data such as articles and books and stuff. The research is almost conclusively kept that in the society 5.0 era, technological growth is increasing, and even more plausibly in cyberspace, it can make it easy for people to do things that go from sharing information to sharing information, with mainstream social media users being exploited by the millennials at the moment, looking at the overwhelming majority of youth-oriented social media users. Allowing radical groups to exploit this situation to influence millennials who must be extremely powerful. As for the effort that the millennials are able to counteract radicalism, social media literacy, by filtering out the information that is obtained first, does not accept the teachings received through the world; contribute to science by producing radical-related works so that others will also know about the radicalism and always make use of time with positivity